The Using E-Learning in The English Learning Process on Students’ Writing Descriptive Text During a Pandemic in Ma Ma’arif Nu Assa’adah Bungah Gresik Grade X - Agustina, Lisa; Yumairoh, Vera Resti; Munafiyah, Munafiyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
This study aims to determine 1) the role and function of E-learning and the added value obtained by students from the use of (E-Learning) during the pandemic at Ma'arif NU Assa'adah Bungah Gresik grade x. This research was conducted at the Islamic High School in the village of Bungah, Bungah sub-district. The research method used is descriptive qualitative. The research data were obtained through recorded interviews with 4 informants, namely 3 students and teachers who taught grade X English, classroom observation, documentation, and literature study. This study used the interactive model data analysis technique of Miles and Huberman. The results showed that the role of E-Learning during a pandemic at Ma'arif NU Assa'adah Bungah Gresik grade x was as a facility to support the English learning syllabus at Ma'arif NU Assa'adah Bungah Gresik. Its function is as a means to access (ELearning), as a means of learning that is more interesting and interactive because it brings students closer to information and communication technology devices for learning English, and serves as a means of gathering and discussion for students. Students get added value by using (E-Learning). First, students get a lot of information and study materials, which are up to date easily, quickly, and in more detail. Second, students get information and learning materials in various media formats in the form of text, pictures, and videos that are of interest to them. Third, the students' English skills can develop, especially reading, writing, vocabulary, and grammar skills. Fourth, students are more active and enthusiastic in the learning process because they are directly involved in the process of obtaining information and learning materials needed in learning English. Keywords: information and communication technology, pandemic, learning, media,